A aventura do reino encantado : a representação do sertão no romance d'A Pedra do Reino de Ariano Suassuna - Paula, Keynny Lina Dala Bernardina de (2016)
The presente dissertation has by objective analise the representation of sertão in the novels Romance d’A Pedra do Reino e o príncipe do sangue do vai-e-volta (1971), by Ariano Suassuna, having as theoretical support the conceptual notions of representation, appropriation and cultural practices to the perspective of New Cultural History. It was considered the cultural practices of Ariano Suassuna and the appropriation of oral and written popular culture texts. The vision of rural and archaic Brazil is built inside the novel through the representation of sertão as a place of confirmation of national identity, where the real Brazilian culture keeps intact to the detriment of globalized culture of big urban centers – being in evidence through the intertextuality kept by the northeast popular novelist and the literature of chivalry.